RUMAH “SAKIT JIWA” (TEATER MODERN) - Suprianda, Andicky; Tulus Handra Kadir (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This artwork aims to interpret the phenomena and behavior of people in a mental hospital. The creation process involves observation (exploration), improvisation, and formation. The idea for the theatrical work "Rumah Sakit Jiwa" (Mental Hospital) is derived from the behavior of people inside a mental hospital. Mental illness, as a creative idea, influenced the director's imagination, which was then translated into a working concept that became the foundation for the three-part procession in this work.